“The Actions and Activities of the Internal (secret) French Resistance from 1943 until the Beginning of the Implementation of the Normandy landings in June” 1944 - Mohamed Khudair, Rabha; Abdul Muttalib Mohammed Hassan, Ayoub (Journal of College of Education, 2021)
The world witnessed the Second World War, which lasted nearly six years, during which the most advanced and deadly weapons were used, Which led to the occupation of many European countries, especially France, which was occupied by Germany on June 14, 1940. This led to the emergence of the internal (secret) French resistance. It aimed to get rid of the German invasion through several activities and notable actions it carried out through printing and publishing (secret resistance newspapers), using guerrilla warfare, sabotage and espionage methods, and through resistance (workers and the French countryside). Until the French entered the Allied forces on August 25, 1944, the yoke of the German occupation that lasted nearly four years.